(untitled) (Al-Farooq Journal of Sciences, 2026)
This research addresses the ongoing debate between human and artificial intelligence from a critical philosophical perspective, focusing on three main axes: First, the fundamental difference between "knowledge" as a conscious human act and "processing" as an algorithmic, automatic process. Second, a critique of "instrumental rationality," which could transform artificial intelligence from a tool serving humanity into an authority dictating its ethical and cognitive choices. Third, the study explores the possibility of creating a new "synthesis" that combines unbridled human creativity with pattern-bound machine intelligence. The research concludes that despite its computational superiority, artificial intelligence still lacks "self-criticism" and "intentionality," making the critical role of humans an indispensable moral and epistemological guardian in this digital age. The research problem lies in the risks arising from reducing the human mind to algorithmic dimensions, which threatens human autonomy and moral agency. The research adopts a critical analytical approach, drawing inspiration from Immanuel Kant’s theories on the limits of knowledge and the Frankfurt School’s critique of instrumental reason. The research concludes that artificial intelligence, despite its computational efficiency, lacks "judgmental power" and contextual awareness, necessitating the development of a "critical ethics" that ensures technology remains a tool for serving human goals, not a replacement for them.